Competition Law in Thailand: A Prelimary Analysis - Sakda Thanitcul (Washington University Global Studies Law Review, 2002)
The author interviewed a number of high-ranking MOC officials and representatives of Thai businesses and there are conflicting views about who originally backed the current Thai Trade Competition Act (TCA). MOC officials insist that Thai officials initiated the idea of creating the TCA, but representatives of Thai industries believe the Thai government initiated it under pressure from the United States. The author learned from interviewing key members of the Working Committee that the Working Committee modeled substantial parts of the TCA after the South Korean Monopoly Regulation and Fair Trade Act (MRFTA), the Taiwanese Fair Trade Law (FTL), the Japanese Antimonopoly Law of 1947, and the German Act Against Restraints of Competition
Keywords: Thailand; Price fixing; Monopolies; Competition (Economics)